The Dynamics of Vehicles on Roads and Tracks 2016
DOI: 10.1201/b21185-60
|View full text |Cite
|
Sign up to set email alerts
|

The unification of acceleration envelope and driveability concepts

Abstract: This work aims to study which level of detail should be preserved in the multibody modelling of a racing car in order to obtain reliable results without excessive model complexity. Three multibody models have been developed and compared through optimal control simulations. The models differ from each other for the order of dynamics comprised: starting from a 14 degrees of freedom (dof) car which includes chassis and wheels motion, a 10 dof model model is obtained by neglecting the wheels hop dynamics, finally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…The model developed here abandons the QSS tyre load simplification since it has been showed that it negatively influences simulations outcomes. 18 Moreover, suspension kinematics are taken into consideration because they have a relevant influence on vehicle performance. 24,25 A car model that includes this features leads to a relatively complex lap time OCP, that may be very difficult to solve.…”
Section: Multibody Model Of the Gp2 Carmentioning
confidence: 99%
See 3 more Smart Citations
“…The model developed here abandons the QSS tyre load simplification since it has been showed that it negatively influences simulations outcomes. 18 Moreover, suspension kinematics are taken into consideration because they have a relevant influence on vehicle performance. 24,25 A car model that includes this features leads to a relatively complex lap time OCP, that may be very difficult to solve.…”
Section: Multibody Model Of the Gp2 Carmentioning
confidence: 99%
“…Indeed such terms are related to small inertial forces (less than 0 . 1 times the inertial force related to z ·· as ) that do not play an important role in time simulations. 18 On the contrary, the terms related to the ratio between variables in u as and z as are required to take into account the anti-lift, anti-squat or scrub behaviour of the suspension and are relevant even in determining the stationary trim of the suspension or of the vehicle. 24,25…”
Section: Multibody Model Of the Gp2 Carmentioning
confidence: 99%
See 2 more Smart Citations
“…The minimum time problem is formulated here as an optimal control problem with the same approach presented in [26], [25], [24], and will be briefly summarized here. The Optimal Control Problem (OCP) consists in finding the vehicle control inputs u s that drive the vehicle from the starting grid line s 0 to the end s f of the TT course in the minimum time, while satisfying a set of differential equality and algebraic inequality constraints.…”
Section: Optimal Control Problem Formulationmentioning
confidence: 99%